2023
DOI: 10.1021/acs.nanolett.2c03779
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Free Super-Liquid-Repellent Surfaces: Pushing the Limits of PDMS

Abstract: Methods for fabricating super-liquid-repellent surfaces have typically relied on perfluoroalkyl substances. However, growing concerns about the environmental and health effects of perfluorinated compounds have caused increased interest in fluorine-free alternatives. Polydimethylsiloxane (PDMS) is most promising. In contrast to fluorinated surfaces, PDMS-coated surfaces showed only superhydrophobicity. This raises the question whether the poor liquid repellency is caused by PDMS interacting with the probe liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Glass slides (24 × 60 mm 2 , 170 ± 5 μm thickness, Menzel−Glaser) were coated with PDMS pseudobrushes, using the "grafting-from" 78 and the "grafting-to" 35 approaches. In short, grafting-from implies the polymerization of vaporous monomers from grafting sites on the surface while prepolymerized chains are grafted-to grafting sites.…”
Section: ■ Experimental Setupmentioning
confidence: 99%
“…Glass slides (24 × 60 mm 2 , 170 ± 5 μm thickness, Menzel−Glaser) were coated with PDMS pseudobrushes, using the "grafting-from" 78 and the "grafting-to" 35 approaches. In short, grafting-from implies the polymerization of vaporous monomers from grafting sites on the surface while prepolymerized chains are grafted-to grafting sites.…”
Section: ■ Experimental Setupmentioning
confidence: 99%
“…Furthermore, to provide materials with waterproof properties, the grafting of polydimethylsiloxane (PDMS) or fluorine-containing chains is generally adopted because of their low surface energy. 26–31 Notably, fluorine-containing compounds generally possess a lower surface energy than PDMS, indicating a better waterproof performance. In addition, previous reports have revealed that various liquids can slide off on fluorine-modified rough surfaces, whereas, oily liquids would compromise the waterproof property of PDMS-modified rough surfaces, suggesting that fluorine-modified porous materials are more suitable for applications in harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The application of superhydrophobic coatings in oil-contaminated environments is restricted since these coatings, even with basic micro-and nano-rough structures, are frequently unable to repel oil and other liquids with a surface energy lower than water [20,21]. In order to expand the coating's wettability resistance from water to oil, the concept of superamphiphobic surfaces has emerged, i.e., the contact angle of both water and oil is greater than 150 • , and the sliding angle of both water and oil is less than 10 • [22][23][24]. and the generally accepted prerequisites for the development of superamphiphobic surfaces-that is, materials with extremely low surface energy and specifically designed surface structures [20], like kangaroo, overhanging [13], and re-entrant structures [25,26]-have been established.…”
Section: Introductionmentioning
confidence: 99%